2007
DOI: 10.1007/s10531-007-9264-5
|View full text |Cite
|
Sign up to set email alerts
|

Importance of semi-natural habitats for the conservation of butterfly communities in landscapes dominated by pine plantations

Abstract: While the area of plantation forests continues to increase worldwide, their contribution to the conservation of biodiversity is still controversial. There is a particular concern on the central role played by natural habitat remnants embedded within the plantation matrix in conserving species-rich insect communities. We surveyed butterXies in maritime pine plantation landscapes in south-western France in 83 plots belonging to seven habitat types (Wve successional stages of pine stands, native deciduous woodlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 53 publications
1
22
0
3
Order By: Relevance
“…Apart from land use and farm management methods or farming practices (Weibull and Östman 2003), vegetation structure, quality of the matrix surrounding an agricultural habitat (Binzenhöfer et al 2008;Summerville et al 2008), diversity and types of habitats (Dessuy and de Morris 2007;Ngai et al 2008;Kumar et al 2009), landscape heterogeneity and habitat connectivity (Davis et al 2007) are important factors determining occurrence, movements, population dynamics, seasonality, persistence and longterm survival of Lepidoptera faunal communities in the agricultural landscapes (Dennis 2003;Greza et al 2004;Chay-Hernández et al 2006;Kivinen et al 2008;Öckinger and Smith 2008;Pickens and Root 2008;Stasek et al 2008;Dover and Settele 2009;Brückmann et al 2010). Generally, agricultural matrices that are more resembling a nearby forest patch maintain higher butterfly diversity than matrices with lesser shade cover (Summerville et al 2001;Kitahara and Watanabe 2003;Weibull and Östman 2003;Boriani et al 2005;Aviron et al 2007;Ohwaki et al 2007Ohwaki et al , 2008Barlow et al 2008;Bergman et al 2008;van Halder et al 2008;Marín et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Apart from land use and farm management methods or farming practices (Weibull and Östman 2003), vegetation structure, quality of the matrix surrounding an agricultural habitat (Binzenhöfer et al 2008;Summerville et al 2008), diversity and types of habitats (Dessuy and de Morris 2007;Ngai et al 2008;Kumar et al 2009), landscape heterogeneity and habitat connectivity (Davis et al 2007) are important factors determining occurrence, movements, population dynamics, seasonality, persistence and longterm survival of Lepidoptera faunal communities in the agricultural landscapes (Dennis 2003;Greza et al 2004;Chay-Hernández et al 2006;Kivinen et al 2008;Öckinger and Smith 2008;Pickens and Root 2008;Stasek et al 2008;Dover and Settele 2009;Brückmann et al 2010). Generally, agricultural matrices that are more resembling a nearby forest patch maintain higher butterfly diversity than matrices with lesser shade cover (Summerville et al 2001;Kitahara and Watanabe 2003;Weibull and Östman 2003;Boriani et al 2005;Aviron et al 2007;Ohwaki et al 2007Ohwaki et al , 2008Barlow et al 2008;Bergman et al 2008;van Halder et al 2008;Marín et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The predominance of highly mobile species may decrease the correlation between local deadwood measurements and saproxylic beetles diversity (Jonsson et al, 2005;Nilsson and Baranowski, 1997). Moreover, in Maritime pine forests it has been shown that wider landscape variables were as important as stand level attributes when assessing local species assemblages of birds, carabids, spiders (Barbaro et al, 2005) and butterflies (Van Halder et al, 2008).…”
Section: "Environmental" Indicatorsmentioning
confidence: 99%
“…Pertanto, mentre nelle aree dominate da conifere i Lepidotteri legati allo strato erbaceo sono comunque presenti a prescindere dalla composizione del paesaggio, questi possono entrare a far parte delle comunità delle latifoglie in maniera apprezzabile solo se nel paesaggio sono presenti delle patch di zone aperte. Come osservato anche da Van Halder et al (2008), le differenze nella struttura delle comunità di Lepidotteri dipendono in massima parte dalla composizione della vegetazione del sottobosco piuttosto che dal tipo di habitat. Questo è risultato particolarmente vero per le specie le cui larve sono troficamente legate alle graminacee.…”
Section: Discussioneunclassified
“…Un maggiore dettaglio delle caratteristiche paesaggistiche anche a piccola scala è necessario nella determinazione dei fattori che influenzano le comunità dei Lepidotteri. Come osservato in altri studi, è bene tenere in conto le caratteristiche sia dei singoli habitat che del paesaggio circostante, poiché la diversità ecologica risente degli effetti del paesaggio a scale differenti (Weibull et al 2000, Schneider & Fry 2001, Van Halder et al 2008. La tutela di habitat di ridotte superfici è importante per una corretta redazione dei piani di gestione delle aree protette, i quali devono prevedere interventi mirati alla protezione di questi habitat che possono ospitare specie di importanza conservazionistica.…”
Section: Discussioneunclassified
See 1 more Smart Citation